Obtenção do extrato volátil de sementes de Anethum graveolens L. por diferentes técnicas extrativas - Garcez, José Jacques (2016)
This master thesis aimed the study of different extraction techniques and the influence of different particle sizes in maximizing the yield of essential oil from the seeds of dill, an herb widely used in cooking and in traditional folk medicine and has a wide range of properties conferred such as antimicrobial, antibacterial and antioxidant. The techniques used for obtaining the essential oil were extracted by steam distillation and hydrodistillation, where different average particle sizes of crushed seed and anise were considered, and extraction with supercritical carbon dioxide, where besides the variation of average particle sizes it was used different pressure values. For the supercritical extraction, it was then used the response surface method in which the variables pressure and average particle diameter were investigated, also a 2² factorial design was used to determine the number of experiments required. The best conditions for the three extractive methods were found, being larger diameters of particles to steam distillation and hydrodistillation, and 10,000 kPa and smaller diameter particles to the supercritical extraction. In this evaluation, it was performed mathematical modeling of the yield versus time curves of the best extraction conditions for each of the techniques. The extracts were analyzed in a gas chromatograph coupled to a mass spectrometer, after, the results have undergone a statistical analysis of major components, which were divided into 3 different groups according to their similar compositions. Finally, its antibacterial activities were tested where all extracts showed activity against E. coli.